Identifying novel inhibitors against drug-resistant mutant CYP-51 Candida albicans: A computational study to combat fungal infections - Saadia Jabeen; Muhammad Umer Khan; Hasan Ejaz; Shakeel Waqar; Aisha Farhana; Muharib Alruwaili; Yasir Alruwaili; Abualgasim Elgaili Abdalla; Sahar Mudassar; Qurban Ali (PLoS ONE, 2025)
Candida albicans (C. albicans) is an opportunistic pathogen in immunocompromised individuals and a normal inhabitant of the oral cavity, throat, gastrointestinal tract, and genitourinary system among health populations. Our study focused on identifying new inhibitors capable of binding to the mutant cytochrome P450 family 51 (CYP-51) protein and intended to be effective against resistant C. albicans infections. The pharmacophore ligand-based model was used for the virtual screening of compound libraries. Molecular docking was performed on Maestro, Schrodinger. ADMET analysis was performed to check drug-likeness properties. Density function theory (DFT) calculations, molecular dynamic (MD) simulation, and free binding energy (MMPBSA) were also calculated. For docking, six compounds were selected from 11,022 hits from PubChem libraries, which showed the best interaction with mutant CYP-51 and were identified by pharmacophore mapping performed with the Pharma IT tool. Each of the six compounds was docked into the active site of the mutant CYP-51 protein. Overall, CP-3 exhibited significant binding affinity (−10.70 kcal/mol) as well as, showed good ADMET characteristics such as drug-likeness, absorption, distribution, metabolism, excretion, and toxicity. The lead compound, CP-3, was further used for MD simulation to observe the dynamic behavior of the complex in the active site of the mutant CYP-51 protein. Computational studies indicated that CP-3 could be a useful antagonist for the mutant protein, CYP-51. This study used computational approaches to identify potential inhibitors of C. albicans by targeting CYP-51 for antifungal drug development. Further invitro and in vivo studies are needed to evaluate its pharmacokinetic properties and efficacy as a novel antifungal drug.